2014
DOI: 10.1653/024.097.0226
|View full text |Cite
|
Sign up to set email alerts
|

First Study of Host-Plant Preferences ofSinopla perpunctatus(HEMIPTERA: Acanthosomatidae), a Stink Bug from the Andean-Patagonic Forest

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Therefore, in addition to developing a theoretical framework for the understanding of the insects inhabiting the native forest, this information also provides a starting point for phytosanitary care and the conservation of systems containing native species (Schowalter ; Altmann ; Pietrantuono et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, in addition to developing a theoretical framework for the understanding of the insects inhabiting the native forest, this information also provides a starting point for phytosanitary care and the conservation of systems containing native species (Schowalter ; Altmann ; Pietrantuono et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…; Pietrantuono et al . ). Such studies (common in biological control trials) contribute to understanding in a variety of different ways by providing knowledge regarding the ecology and natural history of native phytophagous insects and information that can be used for the development of conservation plans and even for the silvicultural management of different species of Nothofagaceae.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, when laboratory preference tests were performed on native phytophagous insects by offering to choose between hosts or habitats covered with volcanic ash the results were mixed: Pietrantuono et al . () found no effect of the ash in the host preference test of a shield bug ( Sinopla perpunctata ), but in Pietrantuono et al . (unpublished data), leafminers avoided volcanic ash as a pupation site.…”
Section: Resultsmentioning
confidence: 94%
“…Several studies have demonstrated that susceptibility of insects to ash produced a decrease in population level (Akre, 1980;Akre et al, 1981;Shanks & Chase, 1981;Masciocchi et al, 2013), and that the life-expectancy of insects forced to ash exposure was reduced both in exotic (Buteler et al, 2011), and native species (Fernández-Arhex et al, 2013. On the other hand, when laboratory preference tests were performed on native phytophagous insects by offering to choose between hosts or habitats covered with volcanic ash the results were mixed: Pietrantuono et al (2014) found no effect of the ash in the host preference test of a shield bug (Sinopla perpunctata), but in Pietrantuono et al (unpublished data), leafminers avoided volcanic ash as a pupation site. Contrary to the case of exotic pests such as Vespula spp.…”
Section: Resultsmentioning
confidence: 99%
“…First, we performed a Wilcoxon matched pair test (Bonferroni corrected) to determine whether there were differences between treatments and second we developed a model using a Bayesian approach to establish a scale of preferences between stimuli. This procedure provides a more straightforward way to determine the degree of attraction between stimuli and it is widely used by ecologists in animal behaviour studies (Ellison, 2004; McNamara et al , 2006; Valone, 2006; Pereira et al , 2013; Pietrantuono et al , 2014, 2015, 2017).…”
Section: Methodsmentioning
confidence: 99%